Digital Marketing Strategy Of Msme Mentari Citra Lestari Pangkep Products During The Covid-19 Pandemic - Yunarti Yunarti (Cita konsultindo, 2023)
Covid-19 in 2020 had many impacts on several sectors, one of which was the economic sector. Uncertainty during the COVID-19 pandemic resulted in MSME business actors experiencing a decrease in income. For this reason, MSMEs must have a strategy to survive during the Covid-19 pandemic. Digital marketing strategy is a form of business to promote and introduce a brand and product using digital media. This is the right step to survive during this pandemic. This study aims to determine the digital marketing strategy for UMKM Mentari Citra Lestari to be able to survive during the Covid-19 pandemic. This study uses a qualitative method by selecting a case study. The results of the study show that these MSMEs are implementing digital marketing strategies to survive the Covid-19 pandemic with several strategies, namely 1) Implementing social media marketing, using Instagram and Facebook as marketing media by utilizing photos and videos. 2) Implementing content marketing, these MSMEs use marketing content to help introduce products through features adopted from social media, using messages that are packaged creatively using interesting photos, captions, hashtags and videos.